Water controls the seasonal rhythm of rock glacier flow - Cicoira, Alessandro; Beutel, Jan; id_orcid:0 000-0003-0879-2455; Faillettaz, Jérome; Vieli, Andreas (Earth and Planetary Science Letters, 2019)
ISSN:0012-821X ISSN:1385-013X